The Effect of Online Learning on Learning Interest and Concepts Understanding During the Covid-19 Pandemic - Sofia Kusuma Ramandanti; Woro Sumarni; Sri Susilogati Sumarti (Jurnal Pendidikan Kimia Indonesia, 2022)
The Covid-19 pandemic caused a transformation in the implementation of learning from offline/face to face to online learning. This study aims to analyze the effect of online learning methods on students' learning interest during the Covid-19 pandemic. Online learning is very beneficial for maintaining learning communication between teachers and students. This research is based on the one-group pretest-posttest method. Where the initial ability of students is obtained through the Pretest before the lecture, and student learning outcomes are obtained from the Posttest which is carried out after the lecture using the online method. The research was conducted on 21 students who took acid-base chemistry courses. The data analysis technique used is simple linear regression analysis. From the research results, it was found that the average score of students in the Pretest was 59.5 and the average score of students in the Posttest was 74. Meanwhile, the response results showed that online learning methods had a positive, although not significant, effect on students' interest in learning during the Covid-19 pandemic. This means that the better the quality of online learning, the higher the learning interest of students. The magnitude of the influence of online learning methods on students' learning interest is only 3.8%. That means that even though it is not significant, the lecturer's ability to carry out online learning methods still has an influence on students' interest in learning.